Fostering Voluntary Contributions to a Public Good A Large-Scale Natural Field Experiment at Wikipedia - Jana Gallus (Center for Research in Economics, Management and the Arts (CREMA), 2015)
This natural field experiment tests the effects of purely symbolic awards on volunteer retention in a public goods context. The experiment is conducted at Wikipedia, which faces declining editor retention rates. Randomization assures that receipt of the award is orthogonal to previous performance. The analysis reveals that awards have a sizeable and statistically significant effect on retention. The findings are noteworthy firstly for showing that symbolic awards with no career-related implications can positively impact behavior. Secondly, they indicate that the awards' motivating effect goes beyond serving reputational concerns and even positively affects recipients' private identity.
Keywords: C93; M52; H41; 330